The Application of Discovery Learning Model to Improve the Character of Democracy and Learning Outcomes For Elementary Students - Imada Cahyani Elvirawati; Vanda Rezania (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study's overarching goal is to ascertain whether or not the discovery learning paradigm may improve democratic traits and academic performance. In this study, action research was conducted in the classroom over the course of two cycles. Rural primary schools in Sidoarjo were the focus of this study. Data on learning outcomes were collected using a questionnaire, and data on democratic character value was collected by a test of learning outcomes administered at the end of each cycle. This study made use of descriptive statistics for its analysis of data. Class IV students' learning outcomes and their appreciation for democratic principles both improve with the implementation of this discovery learning paradigm. The calculated mean shows the answer. Over and above the researcher-determined KKM of 75.0, students' democratic character is typically valued at 57.0 after the first cycle, 63.23 after the second, and 77.14 after the third. In addition, the researcher finds that the average value of student learning outcomes rises from 78.0 in the first cycle to 80.47 in the second cycle to 89.04 in the third cycle, all while remaining above the KKM, which is 85.0. The quality of democracy and educational outcomes for students can both benefit from the use of the discovery learning approach.